2021
DOI: 10.1038/s41598-020-80891-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of VOCs in essential oils extracted using ultrasound- and microwave-assisted methods from sweet cherry flower

Abstract: The floral fragrance of plants is an important indicator in their evaluation. The aroma of sweet cherry flowers is mainly derived from their essential oil. In this study, based on the results of a single-factor experiment, a Box–Behnken design was adopted for ultrasound- and microwave-assisted extraction of essential oil from sweet cherry flowers of the Brooks cultivar. With the objective of extracting the maximum essential oil yield (w/w), the optimal extraction process conditions were a liquid–solid ratio of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 50 publications
2
14
0
1
Order By: Relevance
“…Notably, benzaldehyde was found in all cherry by-product extracts in significant amounts ( Table 3 ). These results are in agreement with the study by Zhang et al [ 35 ], who detected this compound and ( E )-2-hexenal in the sweet cherry flowers of cultivars Brooks, Black Pearl, Tieton, and Summit. This benzaldehyde has a sweet, floral, and spice-like odor and is widely used by the cosmetic and food industries as an aliphatic fragrance and flavor material [ 36 ].…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Notably, benzaldehyde was found in all cherry by-product extracts in significant amounts ( Table 3 ). These results are in agreement with the study by Zhang et al [ 35 ], who detected this compound and ( E )-2-hexenal in the sweet cherry flowers of cultivars Brooks, Black Pearl, Tieton, and Summit. This benzaldehyde has a sweet, floral, and spice-like odor and is widely used by the cosmetic and food industries as an aliphatic fragrance and flavor material [ 36 ].…”
Section: Resultssupporting
confidence: 93%
“…2-Ethyl-1-hexanol was the alcohol present in large amounts in most P. avium by-product extracts ( Table 3 ). Compared to other studies, 2-ethyl-1-hexanol was also the predominant alcohol found in cherries [ 5 ] and their flowers [ 35 ]. Phenylethyl alcohol was found mainly in stems and flowers, and it is an important flavoring ingredient.…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…No processo de extração via ultrassom os possíveis parâmetros que influenciam na extração de metabólitos secundários são: concentração da amostra, proporção de solvente, tempo de extração e temperatura (Ghitescu, et al, 2015). Desse modo, a utilização de ferramentas estatísticas, tais como o planejamento fatorial e a superfície de resposta, vêm sendo empregadas, a fim de explorar condições experimentais de sistemas com um menor número de análises (El-Naggar, et al, 2021;Yuan, et al, 2018;Zhang, et al, 2021). O planejamento Box-Behnken por exemplo, é uma metodologia que utiliza tais ferramentas para o auxílio na definição de quais as melhores condições para extração dos analitos de interesse.…”
Section: Introductionunclassified